Whole-Cell or Acellular Pertussis Primary Immunizations in Infancy Determines Adolescent Cellular Immune Profiles - van der Lee, Saskia; Hendrikx, Lotte H.; Sanders, Elisabeth A. M.; Berbers, Guy A. M.; Buisman, Anne-Marie (Frontiers in Immunology, 2018)
Introduction: Pertussis is re-emerging worldwide, despite effective immunization programs for infants and children. Epidemiological studies show a more limited duration of protection against clinical pertussis in adolescents primed with acellular pertussis (aP) vaccines during infancy than those who have been primed with whole-cell pertussis (wP) vaccines. This study aimed to determine whether memory immune responses to aP, diphtheria, and tetanus vaccine antigens following booster vaccinations at 4 and 9 years of age differ between wP- versus aP-primed children. Methods: In a cross-sectional study, blood was collected of DTwP- or DTaP-primed children before, 1 month and 2 years after the pre-school DTaP booster administered at 4 years of age (n=41-63 per time point). In a longitudinal study, blood was sampled of DTwP- or DTaP-primed children before, 1 month and 1 year after a pre-adolescent Tdap booster at 9 years of age (n=79-83 per time point). Pertussis, diphtheria and tetanus vaccine antigen-specific IgG levels, B-cell and T-cell responses were determined. Results: After the pre-school booster vaccination, IgG levels were significantly higher in aP-primed as compared with wP-primed children up till 6 years of age. Before the pre-adolescent Tdap booster vaccination, humoral and cellular immune responses were similar in aP- and wP-primed children. However, the Tdap booster vaccination induced lower vaccine antigen-specific humoral, B-cell and T-helper 1 (Th1) cell responses resulting in significantly lower Th1/Th2 ratios in aP-primed compared with wP-primed children. Conclusions: The memory immune profiles at pre-adolescent age to all DTaP vaccine antigens are already determined by the wP or aP combination vaccines given in infancy, showing a beneficial Th1-dominated response after wP-priming. These immunological data corroborate epidemiological data showing that DTaP-primed adolescents are less protected against clinical pertussis than DTwP-primed children.